Abdominal pain is associated with anxiety and depression scores in a sample of the general adult population with no signs of organic gastrointestinal disease. Issue 9 (21st May 2013) - Walter, S. A.; Jones, M. P.; Talley, N. J.; Kjellström, L.; Nyhlin, H.; Andreasson, A. N.; Agréus, L.
Abstract: Background: Abdominal pain is common in the community, but only a subset meet diagnostic criteria for irritable bowel syndrome (IBS). Although anxiety and depression have been linked to IBS, the role of mood disturbances in the remainder with symptoms remains unclear. We aimed to study the associations between abdominal pain, anxiety, depression, and quality of life in the general population who were free of organic colonic disease by colonoscopy. Methods: Two hundred and seventy‐two randomly selected subjects from the general population, mean age 54 years (27–71), were clinically evaluated, had a colonoscopy and laboratory investigations to exclude organic gastrointestinal (GI) disease. All subjects completed GI symptom diaries for 1 week, the Rome II modular questionnaire, the Hospital Anxiety and Depression Scale, and Short Form 36. Key Results: Twenty‐two subjects were excluded due to organic disease; 1532 daily symptom records were available for analysis in the remainder. Thirty‐four percent (n = 83) recorded at least one episode of abdominal pain on the diary. Twelve percent fulfilled Rome II criteria for IBS. Both anxiety and depression scores were higher in subjects who reported abdominal pain vs those who did not (P < 0.0005 and P < 0.0005). Anxiety and depression scores independently from IBS diagnosis (Rome II) predicted pain reporting and also correlated positively with pain burden. Quality of life scores were generally lower in subjects with abdominal pain. Conclusions & Inferences: Anxiety and depression are linked to functional abdominal pain, not only in subjects with IBS but also in otherwise healthy people with milder, subtle GI symptoms.